Iris passe-murailles et les limites de l’utopie : quelques réflexions sur une épiphanie comique dans les Oiseaux (vv. 1199-1261) - Anne de Cremoux (Pallas, 2009)
The second part of the Birds by Aristophanes includes several scenes in which gods intervene : Iris, then Prometheus and lastly an embassy including Poseidon, Heracles and a tribal god. Those three scenes have often been analysed as one cluster, as the fanciful meeting of worlds separate in principe, and as further assertion, in that new context, of heroic all-mightiness. Now a closes rereading of the scene in which Iris bears Zeus’ message and slipes through the walls of the city of the birds against the order set down by Pisthecairos, calls for a nuancing of the interpretation of comic epiphanies and calls into question the limits of utopia.